2021
DOI: 10.3389/fimmu.2021.691216
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival Microbiome and Specialized Pro-Resolving Lipid Mediator Pathway Profiles Are Correlated in Periodontal Inflammation

Abstract: Failure of resolution pathways in periodontitis is reflected in levels of specialized pro-resolving lipid mediators (SPMs) and SPM pathway markers but their relationship with the subgingival microbiome is unclear. This study aimed to analyze and integrate lipid mediator level, SPM receptor gene expression and subgingival microbiome data in subjects with periodontitis vs. healthy controls. The study included 13 periodontally healthy and 15 periodontitis subjects that were evaluated prior to or after non-surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 76 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…A study has demonstrated that the species Anaeroglobus geminatus are associated with the four lipid mediators in human periodontitis ( Lee et al., 2021 ). To the best of our knowledge, inflammation is a hallmark of cancer, and the level of lipid mediators has a relationship with different cancers such as oral cancer, gastric cancer, melanomas, pancreatic cancer, colon cancer, liver cancer, and lung cancer ( Sulciner et al., 2018 ; Biswas et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study has demonstrated that the species Anaeroglobus geminatus are associated with the four lipid mediators in human periodontitis ( Lee et al., 2021 ). To the best of our knowledge, inflammation is a hallmark of cancer, and the level of lipid mediators has a relationship with different cancers such as oral cancer, gastric cancer, melanomas, pancreatic cancer, colon cancer, liver cancer, and lung cancer ( Sulciner et al., 2018 ; Biswas et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here we explored the association between genera and blood routine indicators. Anaeroglobus geminatus is positively correlated with different lipid mediators which are related to the inflammatory process of periodontitis ( Lee et al., 2021 ). We also observed that the relative abundance of Anaeroglobus was positively correlated with lymphocyte counts, indicating that dysbiosis of periodontal-associated microorganisms may accelerate the process of inflammatory between periodontitis and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…By integrating 16S rRNA metagenomic sequencing and metabolomics, many abnormally expressed metabolites were found to be positively correlated with periodontal pathogens such as Porphyromonas, Prevotella , and Fusobacterium species ( Na et al, 2021 ). Similarly, a strong correlation was found between lipid mediators and subgingival microbiome profile, suggesting that inflammation induced by lipid mediators significantly affected the microbial composition in periodontitis ( Lee et al, 2021 ). Metabolomics might also be used for evaluating the therapeutic efficacy.…”
Section: Monitoring the Onset And Progression Of Periodontitis With Proteomics And Metabolomicsmentioning
confidence: 98%